2019
DOI: 10.1186/s13293-019-0223-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific influence on cardiac structural remodeling and therapy in cardiovascular disease

Abstract: BackgroundCardiovascular diseases (CVDs) culminating into heart failure (HF) are major causes of death in men and women. Prevalence and manifestation, however, differ between sexes, since men mainly present with coronary artery disease (CAD) and myocardial infarction (MI), and post-menopausal women predominantly present with hypertension. These discrepancies are probably influenced by underlying genetic and molecular differences in structural remodeling pathways involved in hypertrophy, inflammation, fibrosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 89 publications
3
57
0
Order By: Relevance
“…To examine collective associations of up-and down-regulated signaling pathways, a network model describing interaction among the differentially expressed genes was reconstructed ( Figure 4F). The network has shown that metformin treatment inhibits increased inflammation and apoptosis by lowering the Tgf-β/BMP signaling pathway Metformin has also been shown to promote cell proliferation and anti-apoptosis by increasing the Jak/Stat and AMPK-PGC1α signaling pathways ( Figure 4F,G) [19]. Taken together, these data suggest promising positive effects of metformin on myocardial I/R injury, consistent with previous findings [20,21].…”
Section: Metformin Treatment Results In Changes Of Multiple Cellular supporting
confidence: 89%
“…To examine collective associations of up-and down-regulated signaling pathways, a network model describing interaction among the differentially expressed genes was reconstructed ( Figure 4F). The network has shown that metformin treatment inhibits increased inflammation and apoptosis by lowering the Tgf-β/BMP signaling pathway Metformin has also been shown to promote cell proliferation and anti-apoptosis by increasing the Jak/Stat and AMPK-PGC1α signaling pathways ( Figure 4F,G) [19]. Taken together, these data suggest promising positive effects of metformin on myocardial I/R injury, consistent with previous findings [20,21].…”
Section: Metformin Treatment Results In Changes Of Multiple Cellular supporting
confidence: 89%
“…Sex differences in human disease are usually attributed to sex specific life experiences, and sex hormones that influence the function of susceptible genes throughout the genome. [1][2][3][4][5] Such factors do account for some dissimilarities. However, a major cause of sex-determined expression of disease has to do with differences in how males and females transcribe their gene-rich human X chromosomes, which is often underappreciated as a cause of sex differences in disease.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing attention to potential sex differences in cardiovascular biology and disease in studies of animal models and human patients (17,23,31,38). In the current study, we evaluated the effects of cardiac IR injury on female and male pigs prior to sexual maturity (39).…”
Section: Discussionmentioning
confidence: 99%
“…These data provide initial evidence that prepubertal female and male pigs may respond differently to cardiac surgery, with prepubertal female pigs being predisposed to a greater detrimental response. In many studies of cardiac injury response in mice and humans, males are predominantly studied due to their greater fibrotic response to cardiac injury (16,17,27). In adult females of reproductive age, estrogen signaling is antifibrotic and cardioprotective after cardiac injury (14,15,33), but may be less effective prior to puberty or after menopause.…”
Section: Discussionmentioning
confidence: 99%